Contribution of austenite-martensite transformation to deformability of advanced high strength steels: From atomistic mechanisms to microstructural response. (1st September 2018) - Maresca, F.; Kouznetsova, V.G.; Geers, M.G.D.; Curtin, W.A.
Abstract: Steels combining austenite (fcc) with lath martensite (bcc) in nanolaminate microstructures are tough, resistant to hydrogen-embrittlement, and inexpensive, making them attractive for many technological applications. Austenite provides plastic deformation while martensite provides strength, but the nanoscale processes that control plasticity in the austenite layers are not fully established. Recent atomistic simulations and crystallographic theory reveal a unified understanding of the structure and motion of the fcc austenite-bcc (lath) martensite interface in steels, with transformation strains up to ∼ 90 % in Fe-C alloys. In this paper, the atomistic behaviour is connected to the ductility of nanolaminate microstructures. First, the mechanical response of the atomistic fcc/bcc interface under shear loading is analyzed. The interface motion follows a Schmid-type law for resolved shear stresses in the transformation direction. Furthermore, the forward fcc-to-bcc transformation is spontaneous while the reverse bcc-to-fcc transformation requires high stress. The asymmetry correlates well with the Peierls stresses for fcc and bcc screw dislocations, respectively. Second, the atomistic results guide the formulation of a two-scale continuum model for the phase transformation. The multi-scale strategy adopted here accounts for the relevant nano-scale mechanisms and enables modeling the mechanical response of real martensite microstructures, up to the scale of tens of micrometers - which would be untractable with direct atomistic simulations. Multi-scale simulations show that forward transformation contributes significantly to the apparent plasticity in lath martensite. This reinforces recent work highlighting the importance of such nanoscale austenite films for achieving ductility and toughness in lath martensite. Overall, the present work demonstrates how atomistic insights can directly inform continuum models of microstructural deformation, and points toward directions for material control and optimization to achieve enhanced mechanical performance in these steels. Graphical abstract: Image 1